Effect of pellicle modification with polyphenol-rich solutions on enamel erosion and abrasion - Mailart, Mariane Cintra [UNESP]; Berisha, Ilirida; Reinales, Ana Sofia Arana; Niemeyer, Samira Helena; Borges, Alessandra Bühler [UNESP]; Baumann, Tommy; Carvalho, Thiago Saads (FapUNIFESP (SciELO), 2025)
s: The aim of the study was to compare the effect of salivary pellicle modification with polyphenol-rich solutions containing fluoride on enamel erosion and abrasion. Human enamel specimens (n = 14/group) were assigned to five pellicle-modifying groups: GSE+F (grape seed extract +500 ppm F-); CRA+F (cranberry extract +500 ppm F-); NaF (sodium fluoride solution -5 00ppm F-); Sn+F (commercial solution, SnCl2/NaF/AmF); and DW (deionized water, negative control). The specimens were submitted to 5 cycles, each one consisting of pellicle formation (120μl, 30 min, 37°C, no agitation), followed by pellicle modification with the experimental solutions (5 ml, 2 min, 25ºC, 70 rpm), and subsequent salivary pellicle formation (120 μl, 60 min, 37°C, no agitation). The specimens were then submitted to erosion (1% citric acid, 10 ml, 1 min, pH 3.6, 70 rpm, 25ºC). Subsequently, they were submitted to abrasion with a fluoride-based toothpaste slurry in a toothbrushing machine (50 strokes, 200 g load, 2 min exposed to slurry). The enamel surface was evaluated with an optical profilometer at baseline and after the 5 cycles to assess the surface loss. Data were submitted to Kruskal-Wallis followed by a multiple comparisons test (α = 0.05). Significant differences were found between the tested solutions (p <0.001). The highest surface loss was verified in the DW group (p < 0.001). The other tested solutions (GSE+F, CRA+F, Sn+F, NaF) promoted significant enamel protection against the erosive-abrasive challenges with no differences between them. In conclusion, the modification of salivary pellicle with both polyphenol-rich, commercial solution and fluoride solutions were able to protect the enamel surface from erosion and abrasion.
Keywords: Fluorides; Polyphenols; Tooth Wear; Toothbrushing